The Remarkable Spin-down and Ultrafast Outflows of the Highly Pulsed Supersoft Source of Nova Herculis 2021 - Drake, Jeremy; Ness, Jan-Uwe; Page, Kim L.; Luna, Gerardo Juan Manuel; Beardmore, Andrew P.; Orio, Marina; Osborne, Julian P.; Mróz, Przemek; Starrfield, Sumner; Banerjee, Dipankar P.K.; Balman, Solen; Darnley, Matt; et al. (IOP Science, 2021)
Nova Her 2021 (V1674 Her), which erupted on 2021 June 12, reached naked-eye brightness and has been detected from radio to γ-rays. An extremely fast optical decline of 2 magnitudes in 1.2 days and strong Ne lines imply a high-mass white dwarf. The optical pre-outburst detection of a 501.42 s oscillation suggests a magnetic white dwarf. This is the first time that an oscillation of this magnitude has been detected in a classical nova prior to outburst. We report X-ray outburst observations from Swift and Chandra that uniquely show (1) a very strong modulation of supersoft X-rays at a different period from reported optical periods, (2) strong pulse profile variations and the possible presence of period variations of the order of 0.1-0.3 s, and (3) rich grating spectra that vary with modulation phase and show P Cygni-type emission lines with two dominant blueshifted absorption components at ∼3000 and 9000 km s-1 indicating expansion velocities up to 11,000 km s-1. X-ray oscillations most likely arise from inhomogeneous photospheric emission related to the magnetic field. Period differences between reported pre- and post-outburst optical observations, if not due to other period drift mechanisms, suggest a large ejected mass for such a fast nova, in the range 2 10-5-2 10-4 M o˙. A difference between the period found in the Chandra data and a reported contemporaneous post-outburst optical period, as well as the presence of period drifts, could be due to weakly nonrigid photospheric rotation.
Keywords: Ciencias naturales::Física y Astronomía